2020
DOI: 10.1080/16878507.2020.1728963
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antioxidant, immune enhancement, and antimutagenic efficacy of fennel seed extracts in irradiated human blood cultures

Abstract: Foeniculum vulgare Mill. (commonly known as fennel) is one of the precious spices. Almost all parts of the plant are edible and have powerful interest in phytochemical and pharmacological research. The present study was designed to examine the free radical scavenging potential, oxidative damage preventive activity, and anti-inflammatory effects of traditionally used fennel. It assessed the cytogenetic and biochemical effects of fennel on suppression of the radiation hazards in human blood culture at a working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…MBS700021). All measured immunological parameters were evaluated by sandwich ELISA due to its effectivety and high efficacy in detection according to ( Farid et al, 2019 ; Farid et al, 2020b ; Farid et al, 2020c ; Farid et al, 2020d ). The concentrations of serum interleukin (IL)-6, -8 and -10 were measured by using mouse ELISA kit (ab100712, MBS261967 and ab100697, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…MBS700021). All measured immunological parameters were evaluated by sandwich ELISA due to its effectivety and high efficacy in detection according to ( Farid et al, 2019 ; Farid et al, 2020b ; Farid et al, 2020c ; Farid et al, 2020d ). The concentrations of serum interleukin (IL)-6, -8 and -10 were measured by using mouse ELISA kit (ab100712, MBS261967 and ab100697, respectively).…”
Section: Methodsmentioning
confidence: 99%
“… Foeniculum vulgare Mill. Apiaceae Fennel Seeds and fruits Digestive, reproductive, and respiratory disorders Microbial infections Can reduce bad breath and body odor Glaucoma Galactagogue Improve eyesight Flatulence of infants Carminative and diuretic Farid et al (2020) 14. Cuminum cyminum L. Apiaceae Cumin Seeds and fruits Carminative and hypertension Gastro-protective Antispasmodic Hypertension, hypoglycemic and digestive stimulant Anti-osteoporotic Antioxidant Dyspepsia and allergic rhinitis Respiratory and metabolic disorders Goodarzi et al (2020) ; Perez-Ortiz et al (2020) ; Singh et al (2021b) 15.…”
Section: Ethnomedicinal Uses Of Indian Spicesmentioning
confidence: 99%
“…Kryston et al (51) reported that irradiation led to the induction of ROS and RNS that disrupt the normal redox balance inside the cells leading to severe inflammatory processes. Farid et al (52)(53) reported that many pro-inflammatory cytokines were released shortly after irradiation such as IL -1β, IL-6 and which were of particular importance in radiation toxicity pathophysiology. Farid et al (54) added that cytokines are low molecular weight proteins that have a stimulating or inhibiting effect on immune system cells' proliferation, differentiation and function.…”
Section: Int J Radiat Res Vol 19 No 4 October 2021mentioning
confidence: 99%